2015
DOI: 10.1111/1365-2478.12324
|View full text |Cite
|
Sign up to set email alerts
|

Field testing of modular borehole monitoring with simultaneous distributed acoustic sensing and geophone vertical seismic profiles at Citronelle, Alabama

Abstract: A modular borehole monitoring concept has been implemented to provide a suite of well‐based monitoring tools that can be deployed cost effectively in a flexible and robust package. The initial modular borehole monitoring system was deployed as part of a CO2 injection test operated by the Southeast Regional Carbon Sequestration Partnership near Citronelle, Alabama. The Citronelle modular monitoring system transmits electrical power and signals, fibre‐optic light pulses, and fluids between the surface and a rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
148
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(169 citation statements)
references
References 11 publications
(21 reference statements)
2
148
0
Order By: Relevance
“…To determine the DAS instrument response, we must first convert the DAS strain and seismometer velocity values into a consistent format. Daley et al () showed how the array‐nature of DAS can be used to convert DAS array strain values into particle velocity values in the frequency‐wavenumber (FK) domain utilizing the phase velocity relation c=ωfalse/k. This FK‐rescaling technique reformulates as H(ω)=Vxfalse(ωfalse)false(ω+ηkx+ηfalse)Exxfalse(kx,ωfalse). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the DAS instrument response, we must first convert the DAS strain and seismometer velocity values into a consistent format. Daley et al () showed how the array‐nature of DAS can be used to convert DAS array strain values into particle velocity values in the frequency‐wavenumber (FK) domain utilizing the phase velocity relation c=ωfalse/k. This FK‐rescaling technique reformulates as H(ω)=Vxfalse(ωfalse)false(ω+ηkx+ηfalse)Exxfalse(kx,ωfalse). …”
Section: Methodsmentioning
confidence: 99%
“…Generally, DAS studies have focused on seismic wave phase information, which is sufficient to model seismic wavefield velocities, for example, in vertical seismic profiling (Daley et al, ; Mateeva et al, ), ambient noise velocity inversions (Ajo‐Franklin et al, ; Dou et al, ; Zeng et al, ), and earthquake phase identification (Ajo‐Franklin et al, ; Jousset et al, ; Lindsey et al, ; Yu et al, ). However, true ground motion amplitudes are necessary for many other seismological processing tasks, including full‐waveform inversion, AVO analysis, moment tensor inversion, and attenuation analysis, which the DAS community will likely investigate in the near future (Cole et al, ; Paitz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Borehole seismic methods such as vertical seismic profiles (VSP), 3D-VSP, and continuous active-source seismic monitoring (CASSM) (Daley et al, 2008(Daley et al, , 2015aCheng et al, 2010) have application for higher spatial resolution, better signal to noise characteristics, easier direct calibration, and more rapid time-lapse monitoring near wellbores (Coueslan, 2013). These methods require wellbore access for receiver placement and provide information at generally higher spatial resolution in a more limited subsurface region.…”
Section: Monitoring Technologiesmentioning
confidence: 99%
“…A minimum number of such seismic imaging surveys might consist of one baseline followed by a repeat survey, although as the CGS site activity progresses additional surveys might be beneficial. Advances in technology, such as distributed acoustic sensing with fiber optics, have potential to greatly reduce the cost of repeat surveys via low-cost permanent sensing cables (Daley et al, 2015a).…”
Section: Monitoring Technologiesmentioning
confidence: 99%
“…Despite the success of these DAS field trials, there remain challenges and problems for current DAS acquisition approaches and systems, such as low S/N, lack of transverse wave motion sensitivity and uncertainty in receiver depth, which still limit the application of DAS technology (Daley, 2015). There is also a need for further validation and improvement of DAS recording systems as well as DAS processing workflows, in addition to tests of DAS VSP recording in active wells and full evaluation of their utility and business value.…”
Section: Introductionmentioning
confidence: 99%